(untitled) (Research, Society and Development, 2021)
Objective: To identify in the literature, the teaching strategies for the practice of care in oncology in undergraduate courses in the health area. Methodology: This is an integrative review in the databases: LILACS; BDENF; MEDLINE; CINAHL and Web of Science, published from 2014 to 2020. The descriptors used were: Health Sciences; Oncology; Evaluation of Teaching and Universities (Researched at DeCS). Education, Graduate; Oncology and Universities (Researched at MESH). 11 studies were included in the scope of the present review. Results: 08 teaching-learning strategies were identified, namely: theoretical and practical classes; complementary training through courses and electives; use of active methodologies through the discussion of cases, seminars and educational activities with the population; and academic leagues. As for teaching strategies aimed at the principles and guidelines of the National Policy for the Prevention and Control of Cancer in the Health Care Network, the following approaches were identified: Health promotion, cancer prevention and diagnosis; palliative care and treatment. It is noteworthy that teaching strategies aimed at early detection, surveillance, monitoring and evaluation actions were not identified. Conclusion: The need for further studies in the area is emphasized, with the objective of promoting the discussion of teaching strategies in undergraduate health courses that meet the principles and guidelines of the National Policy for the Prevention and Control of Cancer in the Care Network to the Health of People with Chronic Diseases within the scope of the Unified Health System (SUS).